2014
DOI: 10.21608/eajbsc.2014.13710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of White Tea Extract on Antioxidant Enzyme Activities of Streptozotocin –Induced Diabetic Rats

Abstract: Tea is the second most popular drink in the world after water, and many studies have highlighted the effects of drinking tea. Therefore, the aim of this study was to explore the effects of white tea extract on the antioxidant enzymes activity including superoxide dismutase (SOD), glutathione peroxidase (GSH-px), and catalase (CAT). A significant decrease was observed in serum and liver SOD, GSH-px, and CAT activities in the diabetic control rats compared with the nondiabetic control ones. However, a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
3
6
0
Order By: Relevance
“…This means that the protective effect of peel extracts may act by either directly scavenging the reactive oxygen metabolites, due to the presence of various antioxidant compounds, or by increasing the synthesis of antioxidant molecules. These results are in agreement with the study of white tea extract supplementation in diabetic rats which showed an increase in the levels of antioxidants [43].…”
Section: Discussionsupporting
confidence: 93%
“…This means that the protective effect of peel extracts may act by either directly scavenging the reactive oxygen metabolites, due to the presence of various antioxidant compounds, or by increasing the synthesis of antioxidant molecules. These results are in agreement with the study of white tea extract supplementation in diabetic rats which showed an increase in the levels of antioxidants [43].…”
Section: Discussionsupporting
confidence: 93%
“…CAT is a heme-containing enzyme which catalyses the decomposition of H 2 O 2 to water and O 2 and thus protect the cell from oxidative damage [39]. GPx plays a central role in the catabolism of H 2 O 2 and the detoxification of endogenous metabolic peroxides and hydroperoxides which catalyzes GSH [40].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of a white tea extract to rats with hyperglycemia triggered a significant increase in SOD, CAT, GPX, and GSC-Px levels as well as a decrease in MDA levels in the liver and blood serum, which indicates stimulation of the synthesis of exogenous antioxidative enzymes [126]. Similarly, in a study by Sharifzadeh et al [127], the use of green tea extract in rats with induced diabetes revealed that the experimental factor lowered LPO and total thiol group content but did not influence the TAC level.…”
Section: Antioxidative Activitymentioning
confidence: 95%